Increasing Motivation of Primary School Pupils’ Studying - Прокопчук, Вікторія Ігорівна; Прокопчук, В. І.; Прокопчук, Виктория Игоревна; Prokopchuk, Viktoriia I.; Ревенко, Ірина Валеріївна; Ревенко, І. В.; Ревенко, Ирина Валерьевна; Revenko, Iryna V.; Демченко, Юлія Миколаївна; Демченко, Ю. М.; Демченко, Юлия Николаевна; Demchenko, Yuliya M.; et al. (University of Granada, 2020)
The scientific investigation reveals the topic of increasing the motivation of primary school pupils’ studying, which is relevant today and requires careful study. Data from the Institute of Educational Analytics, the German Internet Portal of statistics Statista, the World Bank and the international organization World Population Review have been used in the context of solving the problem of increasing motivation of primary school pupils’ studying in in Ukraine and Germany. The processing of statistics requires the use of methods of theoretical substantiation, analysis and comparison in the study. According to the World Bank’s education quality rating, Germany was ranked as one of the best countries with a high level of education quality in 2015-2017, and Ukraine ranked the 54th and the 56th places respectively. It has been found that today both in Germany and Ukraine an improvement of pupils’ studying at school is observed, it has been found that in the period of 2016-2018 the number of elementary schools in Ukraine decreased sharply, in Germany during 2008-2018 it has been a similar situation. The results of the series of studies have shown the presence in the practice of the activities of educators, psychologists and scientists, specializing in the study of this issue, a significant number of available and potential ways for increasing motivation. It has been studied the reasons for the learning motivation decrease and the factors influencing it, as well as five levels of learning motivation in primary school. In author’s opinion, the ARCS model is relevant nowadays, because it focuses on the motivational aspects of the educational environment and includes four components of motivation. It has been proved, that it is necessary to provide the innovative teaching methods in Ukrainian school during evaluation process. IT programs, that can improve the learning process and increase motivation in primary education has been presented.

Наукове дослідження розкриває актуальну сьогодні проблему підвищення мотивації навчання учнів початкових класів, що вимагає ретельного вивчення. Дані Інституту аналітики освіти, німецького Інтернет-порталу статистики Statista, Світового банку та міжнародної організації World Population Review були використані в контексті вирішення проблеми підвищення мотивації навчання молодших школярів в Україні та Німеччині. Обробка статистичних даних вимагає використання в процесі дослідження методів теоретичного обґрунтування, аналізу та порівняння. Згідно з рейтингом якості освіти Світового банку, Німеччина була визнана однією з найкращих країн з високим рівнем якості освіти у 2015-2017 рр., А Україна зайняла 54-е та 56-те місця відповідно. Було встановлено, що сьогодні як в Німеччині, так і в Україні спостерігається поліпшення навчання учнів у школі, було виявлено, що в період 2016-2018 рр. кількість початкових шкіл в Україні різко зменшилась, у Німеччині протягом 2008-2018 рр. була подібна ситуація. Результати серії досліджень показали наявність у практиці діяльності викладачів, психологів та науковців, що спеціалізуються на вивченні цього питання, значної кількості доступних та потенційних способів підвищення мотивації. Вивчено причини зниження мотивації навчання та фактори, що впливають на неї, а також п’ять рівнів мотивації навчання у початковій школі. На думку автора, модель ARCS є актуальною сьогодні, оскільки вона фокусується на мотиваційних аспектах освітнього середовища та включає чотири компоненти мотивації. Доведено, що в процесі оцінювання необхідно забезпечити інноваційні методи навчання в українській школі. Представлені ІТ-програми, які можуть покращити навчальний процес та підвищити мотивацію в початковій освіті.

Научное исследование раскрывает актуальную сегодня тему повышения мотивации к учебе школьников младших классов, требующую внимательного изучения. Данные Института образовательной аналитики, Немецкого интернет-портала статистики Statista, Всемирного банка и международной организации World Population Review были использованы в контексте решения проблемы повышения мотивации учащихся начальных классов в Украине и Германии. Обработка статистики требует использования методов теоретического обоснования, анализа и сравнения в исследовании. Согласно рейтингу качества образования Всемирного банка, Германия была признана одной из лучших стран с высоким уровнем качества образования в 2015–2017 годах, а Украина заняла 54-е и 56-е места соответственно. Выявлено, что сегодня и в Германии, и в Украине наблюдается улучшение успеваемости учащихся в школе, установлено, что в период 2016-2018 гг. количество начальных школ в Украине резко сократилось, в Германии в 2008-2018 гг. была похожая ситуация. Результаты серии исследований показали наличие в практике деятельности педагогов, психологов и ученых, специализирующихся на изучении данного вопроса, значительного количества доступных и потенциальных способов повышения мотивации. Изучены причины снижения учебной мотивации и факторы, влияющие на нее, а также пять уровней учебной мотивации в начальной школе. По мнению автора, модель ARCS актуальна в настоящее время, так как она фокусируется на мотивационных аспектах образовательной среды и включает четыре компонента мотивации. Доказано, что в процессе оценивания необходимо обеспечить инновационные методы обучения в украинской школе. Были представлены IT-программы, которые могут улучшить процесс обучения и повысить мотивацию в начальном образовании.
Prokopchuk V. Increasing Motivation of Primary School Pupils’ Studying / V. Prokopchuk, I. Revenko, Y. Demchenko, O. Blaga, V. Tarasova // Journal for Educators, Teachers and Trainers. – V. 11 (1). – University of Granada, 2020. – Р. 19-29.
Keywords: Motivation; Studying (Learning); Primary School; Secondary School of I Degree; мотивація; навчання; початкова школа; середня школа I ступеня; мотивация; учеба (обучение); начальная школа; средняя школа I степени; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education